Therapeutic training: past, present and future - Alexander Sergeevich Ametov (Endocrinology Research Centre, 2012)
Diabetes mellitus is a serious medical and social problem in many countries. Nowadays it is well known that most of therapeutic goalscan hardly be reached without patients willingness to take active part in the process of treatment. Thus therapeutic training in diabetesself-management is a necessity. Today different new options in the field of therapeutic education are developing rapidly. Amongthem are training via internet and other telecommunication systems, electronic diaries, various dose calculators, wizards and?simulators?. Many of such approaches show their clinical and economic effectiveness, thus indicating need for further developmentof this sphere.